Membumikan Teks Agama Ala Nahdlatul Ulama - Muhib Rosyidi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2013)
This article discusses how Bahtsul Masail Institution in Nahdlatul Ulama uses religious texts – the Qur’an and Hadith – independently from the socio-historical context of Muslim community in Indonesia. The main source of this research is Ahkamul Fuqaha: Solusi Problematika Hukum Islam, Keputusan Muktamar, Munas dan Konbes Nahdlatul Ulama (1926-2004). The article finds that as the followers of Shafi‘ites, NU’s treatment with the text of al-Qur’an and Hadith within local tradition has its own characteristics, in some way differ themselves with the Shafi‘ites as a sect. In fact, NU is more likely prefer the local traditions of Muslim society than the religious texts themselves.